Application of oleic acid functionalized magnetic nanoparticles for a highly sensitive and efficient dispersive magnetic solid phase extraction of fenazaquin in almond samples for determination by gas chromatrography mass spectrometry - Turan, Nouha Bakaraki; TugbaZaman, Buse; Bakirdere, Sezgin (ELSEVIER, 2020)
A sensitive and efficient dispersive magnetic solid phase extraction (DMSPE) method was developed to determine fenazaquin at trace level by gas chromatography mass spectrometry. Fenazaquin belongs to the quinolone group of pesticides having an ovicidal activity in some agricultural crops and it is known to cause several adverse health effects. Magnetic nanoparticles were utilized as adsorbents in the extraction process and were synthesized based on the basic precipitation procedure. The Fe3O4 nanoparticles were also functionalized in a nitrogen atmosphere with oleic acid in order to enhance the adsorption capacity. The main parameters that affect the DMSPE preconcentration method including the type and amount of magnetic nanoparticles, type and volume of elution solvent were optimized. Under the optimum conditions, a linear range was obtained between 0.20 and 500 ng/mL and the limits of detection (LOD) and quantification (LOQ) calculated were 0.06 mu g/L and 0.21 mu g/L, respectively. The enhancement in detection power was found to be 793.7. The accuracy of the developed method was tested on diegsted almond samples, spiked at two concentrations and extracted with acetonitrile. The respective percent recovery results calculated for 5.0 and 20 mg/kg spiked samples were 91.2 +/- 0.4% and 109.4 +/- 3.4%.
Keywords: Pesticide; Fenazaquin; Dispersive solid phase extraction; Magnetic nanoparticles; Gas chromatography mass spectrometry; Oleic acid; LIQUID-LIQUID MICROEXTRACTION; MULTI-RESIDUE METHOD; PESTICIDE METABOLITES; WATER SAMPLES; CHROMATOGRAPHY; FRUIT; FOOD; PRECONCENTRATION; QUECHERS; QUANTIFICATION; Chemistry